PENERAPAN ASAS KEPENTINGAN TERBAIK ANAK: TELAAH IJTIHAD HAKIM PENGADILAN AGAMA DALAM PUTUSAN HAK ASUH ANAK - Sheila Fakhria (Institut Agama Islam Negeri Batusangkar, 2022)
The study of child protection in Islam remains an interesting topic in several family law studies. This is because there are several views of scholars and judges related to children's rights such as child custody, inheritance, protection of orphans out of wedlock and so on. This paper discusses the judge's ijtihad in determining child custody in religious court decisions to fulfill children's rights. This paper will focus on analyzing of five court decisions and the judge's legal arguments. This study uses a juridical-normative approach by focusing on the enforcement of provisions related to children's rights and the principle of the best interests of children on the judge's legal attitudes and arguments. The author finds at least two types of arguments used by judges in cases related to lineage and children's rights: legal reasons based on legal-maslahah and maslaḥah sosial based.